Contribuição ao Estudo Mineralógico dos Cristais de Esmeralda do Distrito Mineiro de Campos Verdes, Estado de Goiás - PULZ, GÊNOVA MARIA; BRUM, TANIA MARA MARTINI; JUCHEM, PEDRO LUIZ; D’EL-REY SILVA, LUIZ JOSÉ HOMEM; NETO, LEONEL BARROS; BARRETO, POLYANA (Pesquisas em Geociências, 1998)
The emerald composition of the Campos Verdes mining district (Goiás state) was determined by the infrared spectroscopy with Fourier transform (FTIR) and inductive plasm spectrometry (ICP-MS). The results show that the emerald from this region is characterized by relatively high total iron proportions and weight loss ignition, combined with little amount of alkalis (Na+ >> Cs+ > Li+). The infrared spectrum is defined by type II-H2O vibrations. The integration of chemical data with physical and optical properties makes possible to differentitate the Campos Verdes emerald from those Pakistani gems extracted in the mines of the Mingora, Gujarkili e Makhad, as well as from emeralds from Franqueira (Spain), Itabira (Brazil), Colombia, and from those produced in laboratories.